Project Save Lives: Rapid treatment protocol using peer recovery specialists in the emergency department - Lori A Bilello; Katryne Lukens Bull; Shiva Gautam; Raymond Pomm (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Background: Overdose deaths involving opioids, heroin, and fentanyl-class drugs have dramatically increased in the United States in the last decade. In response to the epidemic, the City of Jacksonville (Florida) and local providers came together and developed a plan to reduce repeat overdoses and deaths called Project Save Lives (PSL). PSL utilized Certified Recovery Peer Specialists (CRPS) to engage overdose victims immediately following opioid overdose reversal and offered medication-assisted treatment, recovery support, overdose prevention services, and transportation to detox/treatment services all initiated within the Emergency Department (ED).  Methods: This is an observational study of opioid related overdose victims who presented at a local health system's two emergency departments from 11/16/2017 to 05/31/2018 and were tracked for 6 months after their initial index visit. Patients were tracked as 2 separate groups: those who were approached by a CRPS during their ED visit and those who did not have contact with a CRPS due to the staffing schedule (intake days versus non-intake days). Data collected included repeat overdoses, substance use treatment services received, and opioid related deaths from the initial index visit. Results: There were 45 individuals seen in the two participating EDs for an opioid related overdose on non-intake days (comparison group) and 101 individuals were seen on intake days (cases). Of the 101 patients that were approached by the CRPS in the ED during the 6 month evaluation period, 32 individuals accessed some type of substance use treatment and of those, 24 received medication assisted treatment. Both groups experienced a decrease in repeat overdoses during the post index visit 6 month period; however, those who declined to participate in PSL included individuals who had multiple overdoses during their post index visit period as compared to those who received treatment through the PSL program.  Conclusions: The PSL program resulted in increasing access to and participation in substance use treatment programs. Immediate engagement by a CRPS with direct linkage to substance use treatment services in the ED is demonstrating to be an effective method in addressing the opioid epidemic. Additional research is needed to evaluate the long-term impact of ED engagement programs.